A sustainability framework for redevelopment of rural brownfields: stakeholder participation at SÃO DOMINGOS mine, Portugal - Sardinha, I. D.; Craveiro, D.; Milheiras, S. (Journal of Cleaner Production, 2013)
Planning the redevelopment of brownfields according to the principles of sustainable development is a significant challenge, particularly for rural brownfields that have little hope of attracting private investment. In this paper, we propose a sustainability framework for rural brownfield redevelopment planning that incorporates the concerns and expectations of stakeholders in the process, aiming at the integration of various forms of place making. This work is part of the ongoing REHMINE project. The area studied is the Sao Domingos mine in southeast Portugal, part of the Iberian Pyrite Belt region. The methodology included the mapping of stakeholders in the Sao Domingos mine redevelopment process; semi-structured interviews with those stakeholders; and content analysis of the interviews. The results from the field were then crossed with a detailed analysis of the literature on brownfield regeneration and validated by a participative process. The outcome was a sustainability redevelopment framework that illustrates how the integration of different perspectives and forms of place making can lead to a locally adapted sustainable development overview that can support the redevelopment planning of a brownfield in a rural setting.